2009
DOI: 10.1007/s10797-009-9117-0
|View full text |Cite
|
Sign up to set email alerts
|

Political economy of prudent budgetary policy

Abstract: The principles of tax smoothing and public debt management with stochastic shocks to future national income are extended for prudence. A prudent government deliberately underestimates future national income and the tax base, especially if the variance and persistence of shocks hitting the tax base are large and the tax rate is high. As a precaution the tax rate is thus set higher and public spending lower to build precautionary buffers. This leads to gradual reductions in debt and debt service over time and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Consequently, a risk exists that the use of these resources would not correspond to voters' fiscal preferences but rather to some budget officials' or elected politicians' personal interests. Indeed, politicians may be merely seeking to create a buffer in order to increase expenditure subsequently for re-election purposes (Bischoff and Gohout 2010;van der Ploeg 2010). Moreover, in some weak and corrupted institutional settings with poor checks and balances, underestimating tax revenue may even be a way for incumbent politicians and officers to conceal the extraction of resources from public budgets (Danninger 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, a risk exists that the use of these resources would not correspond to voters' fiscal preferences but rather to some budget officials' or elected politicians' personal interests. Indeed, politicians may be merely seeking to create a buffer in order to increase expenditure subsequently for re-election purposes (Bischoff and Gohout 2010;van der Ploeg 2010). Moreover, in some weak and corrupted institutional settings with poor checks and balances, underestimating tax revenue may even be a way for incumbent politicians and officers to conceal the extraction of resources from public budgets (Danninger 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Given the prevalence of large coalitions in Swiss cantons, we would not be surprised to find a similar effect. Some authors have also suggested, without testing it explicitly, that the finance minister may play a central role in the implementation of prudent tax revenue budgeting (Goeminne et al 2008;van der Ploeg 2010). Given the characteristics of the budgeting process in Swiss cantons, we also tend to think that the finance minister may play a key role in the determination of tax revenue budgeting errors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a theoretical model, van der Ploeg (2010) shows that the appointment of a strong finance minister can offset the common-pool problem within the government. A strong finance minister with at least as many voting rights as all spending ministers together "can thus control the claims of his spending colleagues and avoid excessive debt accumulation" (van der Ploeg, 2010, p. 311).…”
Section: Strength Of the Finance Minister And Personal Characteristicsmentioning
confidence: 99%
“…It is therefore natural to think that voters will evaluate the competence of the finance minister according to his ability to keep the budget balanced. Furthermore, since each spending minister is responsible for only a share of the budget, the finance minister operates in a context of a deficit bias, the so-called common-pool problem applied to the public budget (Weingast et al, 1981;Velasco, 2000;van der Ploeg, 2010). In such a context, the finance minister has an incentive to underestimate tax revenue irrespective of whether she or he is a left wing or right wing finance minister.…”
mentioning
confidence: 99%